Miniaturization of Time-Gated Raman Spectrometer with a Concave Grating and a CMOS Single Photon Avalanche Diode - Li, Zhiyun (My University, 2015)
Raman spectroscopy possesses the important advantages of non-contact and non-destructive properties in chemical analysis applications. Commercial bench-top Raman spectrometers are bulky, expensive, and limited to laboratory use. Handset Raman spectrometers are commercially available, but still expensive. To extend its field applications such as water quality monitoring and pharmaceutical analyses, there is a growing need for cost reduction and system miniaturization of Raman spectrometers. This work focuses on designing and building a compact and low-cost Raman spectrometer. A key issue of a Raman spectrometer is the detection of a weak Raman signal, especially when a strong fluorescence signal is present. Therefore, challenges in this work include system miniaturization and designing a low-cost and sensitive detection system to measure the weak Raman signal. System miniaturization is approached using a concave grating based wavelength selector. A concave grating could perform both functions of light wavelength separation and focusing without the need for extra mirrors, reducing system size and complexity. The concave grating is designed and fabricated on plano-concave lenses by a low-cost custom holographic technique. Characterization of the custom concave grating proves its light wavelength separation and focusing properties. Addressing cost reduction, a CMOS single photon avalanche diode (SPAD) is selected for its low cost and capability of detecting low intensity light. To achieve fluorescence suppression, the SPAD is operated in the time-gated (TG) mode. The TG-SPAD is implemented in a 130nm standard CMOS technology. Fast gating, generation and readout circuits are designed to gate the SPAD at frequencies up to 100MHz, with a short gate window of 3.5ns. Negligible afterpulsing probability (<1%) for hold-off times longer than 16ns is obtained. A time-gated spectrometer prototype is built combining the concave grating and TG-SPAD. The system achieves timing resolution better than 60ps. Fluorescence suppression is observed by narrowing the detection window of the TG-SPAD, and Raman peaks of Rhodamine B are resolved by the system. The time-gated fluorescence lifetime measurement further proves the efficiency and fluorescence imaging capabilities of the proposed system.